Autopercepção de saúde por pacientes com esquizofrenia que utilizam antipsicóticos atípicos. - Patrícia de Castro Fajardo (2023)
Introduction: Self-perception of health is a global assessment of health status, which can be done objectively as the absence or presence of disease and subjectively through self-perception (or self-assessment) of health, being related to several multidimensional aspects, the main point of which is based on the concept of health constructed by the individual himself. Schizophrenia is a serious, chronic, often stigmatizing mental illness where patients are marginalized and generally not heard by society. Therefore, understanding how these patients perceive their health can help improve actions aimed at these individuals. Objective: To evaluate self-perceived health and identify associated factors in individuals using atypical antipsychotics and using a Pharmacy in the Specialized Component of the SUS. Methods: Crosssectional study, based on the health perception profile of the Schizophrenia Economics and Effectiveness Assessment (SCHEEA) project at the Federal University of Minas Gerais, Brazil. Self-rated health, obtained by the question “How is your health today?”, was analyzed in relation to sociodemographic, clinical and lifestyle aspects, with univariate, bivariate and logistic regression analyses. Results: Of the 447 interviewees, 404 answered the question about health perception, which was positive for 69.1%. In the bivariate analysis, there was a statistically significant association between self-perceived health and gender, skin color, education, per capita income, work, number of children, physical activity, religion, family support, diabetes, use of antipsychotics, mobility, personal care, usual activities, pain/malaise, anxiety/depression. The multivariate logistic regression model showed that the chance of positive self-perception of health increased by 54.9% if the patient was male, 68.3% if the patient had higher education and postgraduate education, 117.5% if the patient had some religion, 217.57% if they had family support. And it reduced by 39.9% if the patient had black or brown skin color, 48.5% if the patient had diabetes, 56.94% if the patient felt pain or discomfort. Conclusion: This study showed a higher prevalence of positive self-perception of health among patients with schizophrenia, which can be explained by the appropriate use of medications, since the majority of patients reported getting their medications for more than 5 years at the CEAF Pharmacy.